Income inequality in pandemic times: an analysis of the decomposition of the Gini Index from PNAD COVID19 - Trovão, Cassiano José Bezerra Marques; Pitombo Leite, Fabrício (Brazilian Keynesian Review, 2021)
This article aims to: 1) assess the first impacts of the pandemic on income inequality in Brazil from the PNAD COVID19 of IBGE; 2) present the contributions of the different sources of income to the composition of the Gini Index; showing its progressive or regressive character; 3) quantify the impact of emergency aid for the evolution of income inequality in this period; 4) measure, from five scenarios, the impact of a possible change in the values of the emergency aid, assuming its continuity in the near future or its complete extinction. The results show that social protection, permanent and emergency, proved to be fundamental for the reduction of inequality. More than that, its extinction or the reduction of the base values, will cause an increase in the concentration of income.